The contemporary view of the nature of school learning and teaching: The socio-constructivist perspective and its practical implications - Pešikan Ana (Psihološka Istraživanja, 2010)
The aim of this paper is to show the nature of the learning process from the perspective of socio-constructivist theory, one of the dominant paradigms in psychology today. In addition to the characteristics of the learning process per se, in this paper we give the practical implications of this theoretical position in the process of school learning/teaching. .